Hematologic and plasma biochemistry values for endangered red knots (Calidris canutus rufa) at wintering and migratory sites in Argentina - D'amico, Veronica Laura; Bertellotti, Néstor Marcelo; Baker, Allan J.; González, Patricia M. (Journal of Wildlife Diseases)
We obtained hematologic and plasma biochemistry values for adult, longdistance migrant Red Knots at their southernmost wintering site in Rio Grande (Tierra del Fuego, Argentina) and at the first stopover site in San Antonio Oeste (Río Negro, Argentina). Lymphocytes (L) followed by heterophils (H) were the most abundant leukocytes. H/L ratio and glucose levels were significantly higher at Rio Grande, possibly because of the stress of migration and molting. Packed cell volume results ranged widely, probably in response to increased oxygen demand for migration. Protein profiles and lipids were higher at the stopover site and attributable to birds storing reserves for subsequent flights. Fil: D'amico, Veronica Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Bertellotti, Néstor Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Baker, Allan J. Royal Ontario Museum; Canadá Fil: González, Patricia M. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina. Fundación Inalafquen; Argentina